Is it me or the circumstances? Examining the relationships between individual differences in causal attributions and dispositions toward ridicule and being laughed at. (15th October 2020) - Brauer, Kay; Proyer, René T.
Abstract: We extend the research on three dispositions toward ridicule and being laughed at, namely, interindividual differences in the fear of being laughed at (gelotophobia), joy in being laughed at (gelotophilia), and joy in laughing at others (katagelasticism), by testing their relationships with attributional styles in two studies. Study 1 ( N = 527) showed that gelotophobia robustly relates to depressive attributional styles that are characterized by internal-stable-global explanations (i.e., oneself) of negative events and external-instable-specific attributions (i.e., chance/luck) of positive events. Study 2 extended and replicated the findings by using data from two independently collected samples ( N = 295 and 241) and a mini-meta-analysis ( N = 536). As expected, the relation between gelotophobia and depressive attributional styles replicated well with small-to-medium effect sizes ( f 2 ≥ 0.08; ηp ≥ 0.13). In contrast, gelotophilia was related to the opposite pattern of attributions but effect sizes were small ( f 2 ≤0.06). Katagelasticism existed widely independently of attributional styles. We discuss our findings with regard to previous research (e.g., on relations with potential biases, well-being, and roles in bullying-type situations) and potential future studies (e.g., reattribution training).